The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1177/15459683211011226
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Split-Belt Treadmill Interventions on Step Length Asymmetry in Individuals Poststroke: A Systematic Review With Meta-Analysis

Abstract: Background Individuals poststroke experience gait asymmetries that result in decreased community ambulation and a lower quality of life. A variety of studies have utilized split-belt treadmill training to investigate its effect on gait asymmetry, but many employ various methodologies that report differing results. Objective The purpose of this meta-analysis was to determine the effects of split-belt treadmill walking on step length symmetry in individuals poststroke both during and following training. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
0
11
0
3
Order By: Relevance
“…We also solicited articles from social media, tables of contents from relevant journals (e.g., NNR), and citations from related systematic reviews. 18,19 We included 20 datasets from 17 studies in our meta-analysis (Figure 1). We identified 8236 studies using the search terms in the above databases and sources.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also solicited articles from social media, tables of contents from relevant journals (e.g., NNR), and citations from related systematic reviews. 18,19 We included 20 datasets from 17 studies in our meta-analysis (Figure 1). We identified 8236 studies using the search terms in the above databases and sources.…”
Section: Methodsmentioning
confidence: 99%
“…We also solicited articles from social media, tables of contents from relevant journals (e.g., NNR), and citations from related systematic reviews. 18,19…”
Section: Methodsmentioning
confidence: 99%
“…This process, if repeated over several exposures, can lead to clinical improvements [213][214][215]. A recent meta-analysis of the literature on split-belt based interventions has revealed that this therapy, when implemented as a long-term training paradigm, has the potential to improve step-length symmetry, while also pointing out the necessity of randomized control trials to further confirm this result [216].…”
Section: Perspectives On the Study And Use Of Locomotor Adaptationsmentioning
confidence: 99%
“…The device was designed to reduce the spatial and temporal gait asymmetries experienced in hemiparetic gait patterns by modifying interlimb coordination during overground walking using a combination of therapeutic mechanisms [31]- [34]. The original design concept was based upon the therapeutic mechanism used in split-belt treadmill training for individuals with asymmetric gait patterns (i.e., augmenting asymmetry with the shorter step length on the faster belt to produce a more symmetrical aftereffect [35]) -but in an overground, portable fashion that would allow more frequent training in a variety of environments. The device was additionally designed to create a subtle destabilization of the non-paretic limb, therefore encouraging greater usage of the paretic limb during the user's gait cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Over time and through repeated use of the device, these altered mechanics result in improved gait patterns, including symmetry and speed, when the device is removed, and the user returns to natural walking with a modi ed gait pattern [31]. The mechanism of this change is an aftereffect that has been well-documented in the literature [35], [37], [38]. The gait device and its associated motion can be seen in Fig.…”
Section: Introductionmentioning
confidence: 99%